2009
DOI: 10.1007/s11119-009-9123-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil organic carbon from soil reflectance: a review

Abstract: Soil organic carbon (SOC) concentration is a useful soil property with which to guide agricultural applications of chemical inputs. To enable this, simple, accurate, rapid and inexpensive methods are needed to produce maps of surface SOC concentrations. Researchers have investigated estimates of soil surface properties from remotely sensed information as a means of rapidly quantifying and monitoring some surface soil properties, such as SOC. The objective of this paper is to review the potential and limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(91 citation statements)
references
References 98 publications
4
74
0
4
Order By: Relevance
“…It was reported that there are necessarily functional linkages among plant biomass, plant residues and SOM. SOM correlates closely with soil quality (Reeves, 1997;Al-Kaisi et al, 2005), which influences plant available nutrients and the ability of soil in absorbing plant nutrients (Chen et al, 2005;Ladoni et al, 2010). Both of them primarily determine plant photosynthetic capacity (Chapin et al, 2011;Janssens et al, 2001) and plant biomass over long term periods.…”
Section: Biological Basis Of the Rersmmentioning
confidence: 99%
“…It was reported that there are necessarily functional linkages among plant biomass, plant residues and SOM. SOM correlates closely with soil quality (Reeves, 1997;Al-Kaisi et al, 2005), which influences plant available nutrients and the ability of soil in absorbing plant nutrients (Chen et al, 2005;Ladoni et al, 2010). Both of them primarily determine plant photosynthetic capacity (Chapin et al, 2011;Janssens et al, 2001) and plant biomass over long term periods.…”
Section: Biological Basis Of the Rersmmentioning
confidence: 99%
“…The main properties modulating the reflectance of bare ground are the different mineral components (the underlying parent material) and soil organic matter (SOM) (Ladoni et al, 2010). The relationship between SOM and reflectance is often assumed to be linear, with SOM being negatively correlated to reflectance up to a saturation limit of around 5% SOM in the top soil layer (Curran, 1985;Ladoni et al, 2010). The maximum change in VIS and NIR reflectance due to SOM (a · C lim , in Eq.…”
Section: Dynamic Background Albedomentioning
confidence: 99%
“…Soil organic carbon (SOC) has considerable influence on soil quality and plant growth, and it governs various physical, chemical and biological processes in the soil environment [1,2]. A rapid and economical method for estimating SOC content can improve environmental monitoring, modeling and precision agriculture [3][4][5].…”
Section: Introductionmentioning
confidence: 99%